The Quality Control Of Deep Foundation ? The New Approach By Non-Destructive Techniques ? Synopsis - K. S. Ho (Deep Foundations Institute, 2010)
With the aid of the advanced electronic devices and micro-processors, the quality control of deep foundations can be carried out by Non-Destructive Tests (NDT). Three methods are presented here: the Sonic Logging, Vibration and Stress Wave Analysis Methods. The principles, equipments used, testing procedures and applications are fully described. The correlation of these methods with the conventional tests (mechanical coring and loading test) are studied to give a better understanding of the methods. Several case histories with the test results obtained from a number of sites in Hong Kong and overseas are discussed to show how the pile quality can be examined and especially, how to confirm the effectiveness of remedial works on a defective pile. Recommendation on the percentage of piles to be tested are given at the end of the paper by using statistical method.